2015
DOI: 10.1111/jace.13962
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Oxidation Testing of MAX Phase Composites in the Cr–Ti–Al–C Quaternary System

Abstract: According to the properties determined for the ternary end-members, MAX phases in the quaternary Cr-Ti-Al-C system could be of interest as protective coatings for nuclear fuel cladding in the case of severe accident conditions. In this study, syntheses of 211 and 312 MAX phase compositions were attempted using pressureless reactions starting from Cr, TiH 2 , Al, and C (graphite) powders. It was observed that both the Ti substitution by Cr in Ti 3 AlC 2 and the mutual solubility of Ti 2 AlC and Cr 2 AlC are lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 62 publications
7
45
0
1
Order By: Relevance
“…The structure consists of the stacking of n “ceramic” layer(s) inserted by an A “metallic” layer . A good number of MAX phase compounds have then been synthesized and the physical properties investigated . For example, the M 2 AX phases with M = (Ti, V, Cr, Nb, Ta, Zr, Hf); A = (Al, S, Sn, As, In, Ga), and X = (N, C) have been studied both experimentally and theoretically because of their attractive properties as stated earlier .…”
Section: Introductionmentioning
confidence: 99%
“…The structure consists of the stacking of n “ceramic” layer(s) inserted by an A “metallic” layer . A good number of MAX phase compounds have then been synthesized and the physical properties investigated . For example, the M 2 AX phases with M = (Ti, V, Cr, Nb, Ta, Zr, Hf); A = (Al, S, Sn, As, In, Ga), and X = (N, C) have been studied both experimentally and theoretically because of their attractive properties as stated earlier .…”
Section: Introductionmentioning
confidence: 99%
“…Mixing of more than one species in one (or more) sublattices in the MAX phase crystal structure potentially has important consequences from the point of view of phase stability. Sufficiently exothermic interactions may lead to the stabilization of ordered phases, as exemplified by the (Cr 2/3 Ti 1/3 ) 3 AlC 2 system [11][12][13]. These compounds in some cases have functionalities that are dramatically different from the parent compounds [14].…”
Section: Introductionmentioning
confidence: 99%
“…the partial substitution of either the M, A or X element by a fourth element). [11,12] The latter is almost limitless in terms of possible combinations. Recently, Naguib et al listed 24 quaternary MAX phases for which at least one composition was already reported in the open literature, [11] some of them also existing with different n values.…”
mentioning
confidence: 99%